PENGARUH KUALITAS AUDIT, KONDISI KEUANGAN PERUSAHAAN, DAN AUDIT DELAY TERHADAP OPINI GOING CONCERN (Students' Journal of Accounting and Banking, 2013)
This study aims to examine the effect of audit quality, the company’s financial condition, and audit delay on Opinion Audit Going Concern acceptance of the manufacturing companies located in Indonesian Stock Exchange. The population used in this study are all manufacturing companies listed in Bursa Efek Indonesia (BEI). The samples obtained by using purposive sampling. Hypothesis testing is done by multivariate analysis using logistic regression the independent variable is a combination of metric and non metric (nominal). This analysis technique does not require normality test and test again the assumption on the independent variables. Logistic regression models, asses model fit, and parameter estimation and interpretation. In thus study, the company’s financial condition has positive influence on the possibility of receiving going concern audit opinion. While the audit quality and audit delay revenues negatively affect the possibility of receiving going concern audit opinion.Keywords: Audit Quality, The Company’s Financial Condition, Audit Delay, Going Concern.